Using COVID‐19 cycle threshold and other lab values as predictors of hospitalization need. Issue 5 (12th February 2021) - Seeni, Ramamahesh; Firzli, Tarek; Riddle, Mark S.; Krasner, Charles; Ashraf, Sara; Siddiqui, Faisal
Abstract: SARS‐COV‐2 (COVID‐19) is a novel virus that has caused over 28 million cases worldwide and over 900, 000 deaths since early 2020, rightfully being classified as a pandemic. COVID‐19 is diagnosed via polymerase chain reaction testing which looks at cycle threshold (CT) values of two genes, N2 and E. This study examined CT values of COVID‐positive patients at the VA hospital in Reno as well as other lab values and comorbidities to determine if any could aid clinicians in predicting the need for hospitalization and higher levels of care. Multiple variables, including N2 CT value, absolute lymphocyte count (ALC), D‐dimer, erythrocyte sedimentation rate, C‐reactive protein, fibrinogen, and ferritin were evaluated for potential associations with N2 CT value as well as required level of care (based on World Health Organization [WHO] ordinal score). The results suggest that patients with a N2 CT value less than 34 are four times more likely to have WHO ordinal scores of 4–8 ( p  = .0021) while controlling for age and comorbidities (DM, cardiac, kidney, and lung disease). Patients of age 55 or greater were 15.18 times more likely to have WHO ordinal scores of 4–8 ( p  = .012) controlling for N2 CT value and comorbidities. Furthermore, patients with ALC less than 1 were 5.88 times more likely to have WHO ordinal score of 4–8 ( p  = .00024). N2 CT values also appear to be associated with many commonly obtained markers such as ALC, white blood cell count, C‐reactive protein, and D‐dimer. Patients with N2 CT values less than 34 were 3.49 times more likely to have ALC values less than 1, controlling for age and comorbidities ( p  = .0072) while patients 55 or older were 6.66 times more likely to have ALC less than 1 ( p  = .027). Finally, this study confirms previous conclusions that patients with advanced age had more severe infections and thus will likely require higher levels of care.